Clinical Significance of Peritoneal Fluid Examination for Free Cancer Cells in Patients Qualified for Surgery for Gastric Cancer - Cieśla, Sławomir; Lisiecki, Radosław; Ławnicka, Agnieszka; Kudliński, Bartosz; Ostrowska, Paulina; Davì, Alberto; Veroux, Massimiliano; Murawa, Dawid (Frontiers in Surgery, 2021)
Background: Peritoneal lavage cytology in patients with gastric cancer may correlate with an unfavorable prognosis. This study evaluated the presence of free cancer cells in the peritoneal lavage of a population of patients with gastric cancer and its correlation with the outcome of surgical treatment. Methods: 100 patients diagnosed with gastric or gastrointestinal junction adenocarcinoma underwent surgery. In all patients, a cytological and immunohistochemical analysis of peritoneal lavage was performed. Based on the presence of free cancer cells (fcc) at cytological and immunohistochemical examination of peritoneal lavage, patients undergoing surgery for gastric cancer were divided into two groups: fcc (+) and fcc (-). Results: a total of 100 patients, 37 women and 63 men with a median age of 65 years, were included in the study. In the entire study group, 16 (16%) patients were positive for the presence of free cancer cells (fcc +) at peritoneal lavage examination. However, in the group of patients who underwent gastrectomy, fcc (+) was found in 10 out of 77 (13%) patients. The presence of cancer cells in peritoneal lavage was a strong predictive factor for unfavorable outcome after surgery, and 1-year and 2-year patient survival were 34% and 0% in fcc (+) patients and 79% and 59% in fcc (-), respectively. Moreover, the presence of free cancer cells was associated with a 5-fold increased risk of death within 2 years after surgery. When analyzing the group of patients undergoing R0/R1 surgery, this difference was even more significant (p<0.0001). Conclusions The presence of free cancer cells in peritoneal lavage may significantly affect the outcome of patients with gastric cancer. Radical surgery in patients with free cancer cells in the peritoneal lavage did not result in a survival advantage. Identification of free cancer cells could help for a better stratification of gastric cancer patients, identifying those patients who could better benefit of a radical surgical treatment, finally improving long-term survival.